FORMY USTROJOWE SPÓŁKI AKCYJNEJ - Michalski, Marek (Zeszyty Prawnicze, 2017)
An Organisational Form of a Joint Stock Company Summary A joint stock company constitutes the most organised and formalised type of a commercial partnership in the Polish law. Its economic significance results from the aim of such a legal construction to conduct huge business ventures requiring an engagement of considerable financial and human resources. Thus, the legislator regulated the topic of a joint stock company in a much detailed manner than in case of other commercial partnerships, including a limited liability company. Hence, a joint stock company is a pure type of an association of capital, without personal elements, which causes that its functioning is subjected to the formalised rules specified by the provisions of the law. These rules not only describe the precise manner of actions during the formation of the joint stock company but also assign three basic stages of the legal being of the company. These stages are described in the legal study as organisational forms of a joint stock company and they include: (i) the stage of organisation, so-called joint stock company in organisation, in which actions aimed at the formation of the company and obtaining of the status of a legal person are being undertaken. At this stage, the company in organisation already has the status of a legal person, therefore it may participate in the legal trade as its participant with full rights; (ii) stage of the proper company, which begins with the moment of registering the company in the court register, which means obtaining the legal personality by the company. From that moment, the joint stock company begins its statutory activity; (iii) stage of the company in liquidation, in which the actions aiming at the termination of the legal being of a joint stock company and its removal from the court register are undertaken.